Bilateral orbital myeloid sarcoma preceding acute myeloid leukemia in an adult: a case report and review of the literature. (December 2016) - Vera-Aguilera, Jesus; Mukarram, Osama; Nutalapati, Prathibha; Mok, Mary; Bulumulle, Anushi; Vera-Aguilera, Carlos
Abstract Background Acute myeloid leukemia is typically a disease of the older population and presents mostly in the fifth decade of life. Myeloid sarcoma is a rare initial presentation of acute myeloid leukemia. Previously it has only been documented in children and younger patients. Case Presentation We present an unusual case of retro-orbital myeloid sarcoma as an initial presentation of acute myeloid leukemia in a 43-year-old Caucasian man, with rearrangement of chromosome 11q23 involving theMLL gene. Conclusions We present an unusual case of retro-orbital myeloid sarcoma as an initial presentation of acute myeloid leukemia in a 43-year-old man, with rearrangement of chromosome 11q23 involving the MLL gene.